Dietary Patterns and Ultra-Processed Foods Consumption in Modern and Traditional Populations in South Sulawesi: An Analysis of Nutritional Status and Body Composition: Dietary Patterns and Ultra-Processed Foods Consumption in Modern and Traditional Populations - Taslim, Nurpudji Astuti; Handayani, Nevi Dwi; Arruan, Wanty; Aminuddin , Aminuddin; Bukhari, Agussalim; Faradillah, Andi; Syauki, A. Yasmin (Nutrición Clínica y Dietética Hospitalaria, 2023)
Backgrounds and aim: Dietary patterns play an important role in the emergence of non-communicable diseases such as obesity, hypertension, and metabolic syndrome. This study aims to examine the impact of ultra-processed food on the nutritional status and body composition of modern and traditional population groups in Indonesia. Methods: The study has received ethical approval from the Research Ethics Commission of the Faculty of Medicine, Hasanuddin University with ethics number No.633/UN4.6.4.5.31/PP36/2022. The inclusion criteria in this study included: people in the Makassar population > 50 years old. Exclusion criteria were (1) having chronic gastrointestinal disease/chronic inflammation, (2) having Diabetes Mellitus, (3) consuming antibiotics in the last 3 months, (4) consuming prebiotics/probiotics, (5) having income > IDR 3,400.000,-, (6) rarely (<1x/week) consumes UPF.About 100 samples were taken from people over 50 years old, where 50 samples were taken from both the modern group and the traditional group. To evaluate the dietary pattern, the diet of the sampling persons was analyzed by using a semi-quantitative Food Frequency Questionnaire (SQ-FFQ), and a 24-hours food recall (FR) to examine the food intake. Body Mass Index (BMI) and Waist Circumference (WC) were used to determine the nutritional status, while the body composition was assessed by Tanita BC 730. Results: According to the scatter plot, the higher the ultra-processed food energy consumed, the higher the BMI, Waist Circumference, and Fat Mass results, with the respective effects of 18.4%, 35.3%, and 13.7%. From this study, it was found that there were significant differences (p<0.05) between the traditional and modern groups in all variables except for height based on the independent t-test found no significant difference (p>0.05). Conclusions: In conclusion, dietary patterns with higher consumption of ultra-processed foods influence the increase of body mass index, waist circumference, and fat mass.